(untitled) (International Journal of Engineering and Computer Science, 2014)
The paper presents water balance of Karup catchment, Denmark using integrated catchment modelling tool MIKE SHE. In the present study, water balance in saturated and un-saturated zone was investigated. Beside this, by changing land use water balance is simulated for Karup catchment. Unsaturated zone water balance is characterized by returning 48% water to the atmosphere as evapotranspiration, 49% as percolation and remaining 3% as un-saturated zone storage change. On the other hand, saturated zone water balance is characterized by flowing 28% water to the river as base flow, 50% as drain to river, 20% as saturated zone storage change and rest of are capillary rise and model error. Model simulation shows subsurface storage change was higher during November to February of each year. Beside this, model shows 1982 was quite dry year with low saturated zone storage. Water balance in Karup catchment will be changed substantially if land use changed from forest and wetland to agricultural use. Model shows, the infiltration will be increased from 49% to 51% which can partly justified by loose soil due to agricultural practice. The storage in the saturated zone will be increased from 20% to 25% and drain to the river will be increased from 50% to 63% consequence of more infiltration. However, subsequently base flow to river will be decreased from 28% to 11%. For proper planning and better management of crops in catchment scale it is worth to have the knowledge about catchment scale water balance. Similar approach can be applied in other catchment to investigate water balance in catchment scale.